PERFORMANCE ANALYSIS OF FOOD CROP, HORTICULTURE AND PLANTATION SUB-SECTORS IN AGRICULTURAL CENTERS ON JAVA ISLAND - Rif’an Hariri (Universitas Muhammadiyah Makassar, 2026)
The food crops, horticulture, and plantation sub-sectors are the pillars of the regional economy. In recent years, there has been a problem in the form of a slowdown in the GRDP growth rate in these three sectors, requiring an evaluation of their performance. This study uses data from the Provincial Statistics Agency (BPS) and the Esteban Marquillash Shift Share method. The results obtained indicate that the performance of the food crops and horticulture sub-sectors requires improvement, while the performance of the plantation sub-sector can be considered good. The food crops and horticulture sub-sectors can survive more due to geographical factors. The implication of this study is that local policymakers need to pay special attention to the food crops and horticulture sub-sectors because their performance has been proven to be less than satisfactory. The contribution of this research is to enrich scientific studies related to the agricultural sector, especially food crops, horticulture, and plantations.